PR STRATEGY AS A BASIS FOR SUBSTANTIATING BUSINESS DECISIONS IN THE SPHERE OF TRADE - ZAKREVSKA, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the role of PR strategy as a fundamental tool for supporting and justifying business decisions in the trade sector under conditions of market volatility, digital transformation, and intensified competition. It is argued that in the contemporary economic environment public relations evolve from a purely communicative function into an integrated strategic mechanism that combines analytical, reputational, managerial, and marketing components. A comprehensive approach to PR strategy formation is proposed, encompassing analysis of the internal and external environment, identification of key stakeholders, assessment of consumer behavior patterns, monitoring of competitive communications, selection of effective communication channels and formats, management of reputational risks, and integration of PR initiatives into the overall business strategy of a trade enterprise. The study systematizes PR strategies according to their spheres of influence, distinguishing reputational, communicational, informational-analytical, social-communicative, anti-crisis, and innovative digital strategies. Such classification enables holistic coverage of all levels of communication activity and ensures coherence between communication policy and managerial decision-making. Special emphasis is placed on the analytical function of PR, which provides data-driven support for forecasting market trends, reducing uncertainty, and enhancing the quality of strategic and operational decisions. Practical cases of Ukrainian retail chains SPAR Ukraine and Varus are analyzed to illustrate the synergistic effect of integrating PR strategies with management systems. These examples demonstrate how digital innovations, social initiatives, communication analytics, and reputation management contribute not only to brand image formation but also to improved efficiency of business processes and adaptability to environmental challenges. As a result, a conceptual model for forming PR strategies in the trade sector is developed, ensuring alignment between communication objectives and business goals, increasing managerial responsiveness, strengthening stakeholder trust, and promoting the sustainable long-term development of trade enterprises.